Persepsi Masyarakat Terhadap Praktik Budaya Politik Identitas Pada Pemilihan Kepala Desa Di Desa Namu Ukur Utara Langkat - Mitha Alvia Rosha, Adeline Pastika Muham, Putri Yohana Damanik, Julia Ivana (Pusdikra Publishing, 2023)
This article or writing aims to find out how the perceptions of the people of North Namu Ukur village regarding the practice of identity political culture in village head elections. The writing of this journal uses In the research the writer uses the Non-Doctrinal Sociological Research method, which means that he will use empirical data obtained through interviews and observations. Field data collection techniques through observation and interview techniques as well as literature such as journals and books as support. This study concludes that identity political culture practices are still found in the people of North Namuukur village, moreover, we still find kinship between the Karo Batak tribes in North Namu Ukur village. for the campaign team for village head candidates to influence the local village community in determining the votes, but after that we also found several informants who still chose village head candidates based on their quality.